PENGARUH TEKNIK RELAKSASI PERNAFASAN TERHADAP PENURUNAN TINGKAT NYERI MENSTRUASI (DISMINOREA) PADA REMAJA PUTRI - Yanti, Ariu Dewi (Universitas Pesantren Tinggi Darul Ulum, 2023)
Dysmenorrhea is menstrual pain originating from the uterus. Of course, this situation greatly impacts young women who experience dysmenorrhea, which interferes with school activities, learning activities, and even completing assignments. There are several factors that can influence the occurrence of dysmenorrhea, namely the age of menarche which is <12 years, nutritional status, history of menstrual pain in the family and psychology. The aim of this study was to explain the effect of breathing relaxation techniques on reducing menstrual pain (dysmenorrhea) in young women. In this study, a sequential analytic design was used with a Quasi Experimental type with a pre and post test design approach with a control group. The population in this study were young women at the Youth Posyandu, Carangrejo Village, Kesamben District, with 70 respondents. The sample in this study were 58 respondents and by using non-probability sampling with purposive sampling. The independent variable is breathing relaxation techniques and the dependent variable is menstrual pain (dysmenorrhea). The instrument in this study used pain scoring sheets, then data analysis used the t-test. The results of the t-test showed that H0 was rejected and H1 was accepted, which is shown by the p value (0.000) meaning that there is an effect of breathing relaxation techniques on reducing menstrual pain (dysmenorrhea). If breathing relaxation techniques are carried out regularly, it can reduce menstrual pain (dysmenorrhea). Because, the movements performed in breathing relaxation techniques during menstruation are distraction and relaxation movements that can inhibit pain impulses due to distraction, so that young women get used to doing breathing relaxation techniques to reduce menstrual pain (dysmenorrhea) so they don't depend on analgesic drugs every time they have menstruation. Keywords: Dysmenorrhea, Breathing relaxation technique, Young women